The representations reflected in the interior design of selected ethnic themed restaurants - Caingles, Jeri Maye D.; Mayo, Adelaida Villaraza (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This study determined how interior design of selected ethnic themed restaurants visually & physically represent ethnic cultures. Likewise, it analyzed the meanings of these representations in reference to the history & culture of the countries represented. The study's framework is of the qualitative and prospective study design. Three (3) different restaurant types of ethnic themes were observed: Persian, Japanese and Thai. Using purposive sampling, the researcher observed, studied and analyzed nine (9) restaurant samples wherein three (3) samples classified under each type of ethnic theme have been chosen. Content analysis was used, in reference to relevant literary sources, to process the data gathered. An observation guide and an interview guide were the primary tools used in this study. The results of the analyzed data revealed that the representations of the Persian themes in these restaurants reflect their undying loyalty and continuous reference to their culture's history. This study also revealed that Japanese restaurant design reflects their integrity towards the use of the natural elements as brought about by their great respect for and desire to be in harmony with nature. Lastly, it revealed that Thai restaurant design ultimately reflects the great importance they give to Buddhism, and all the aspects that revolve around it, as part of their culture. The researcher recommends further studies of the cultural or social representations, individually. Additional interviews with interior designers and foreigners originally from the countries being studied would also be ideal.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Restaurants -- Decoration -- Philippines